Harvesting, storing, and converting carbon from the ocean to create a new carbon economy: Challenges and opportunities - Vibbert, Hunter B.; Park, Ah-Hyung Alissa (Frontiers in Energy Research, 2022)
Ever-increasing anthropogenic CO2 emissions have required us to develop carbon capture, utilization, and storage (CCUS) technologies, and in order to address climate change, these options should be at scale. In addition to engineered systems of CO2 capture from power plants and chemical processes, there are emerging approaches that include the Earth (i.e., air, Earth, and ocean) within its system boundary. Since oceans constitute the largest natural sink of CO2, technologies that can enhance carbon storage in the ocean are highly desired. Here, we discuss alkalinity enhancement and biologically inspired CO2 hydration reactions that can shift the equilibrium of ocean water to pump more carbon into this natural sink. Further, we highlight recent work that can harvest and convert CO2 captured by the ocean into chemicals, fuels, and materials using renewable energy such as off-shore wind. Through these emerging and innovative technologies, organic and inorganic carbon from ocean-based solutions can replace fossil-derived carbon and create a new carbon economy. It is critical to develop these ocean-based CCUS technologies without unintended environmental or ecological consequences, which will create a new engineered carbon cycle that is in harmony with the Earth’s system.